PENGARUH KONSENTRASI ASAM HUMAT DAN BAKTERI LACTOBACILLUS TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG MANIS (Zea mays L. Saccharata) - Putri, Ridho Eka; Fathurrahman, Fathurrahman; Hadi, Ahmad (AGRORADIX : Jurnal Ilmu Pertanian, 2024)
The research aims to determine the effect of humic acid concentration and lactobacillus bacteria on the growth and production of sweet corn. The research was conducted at the Universitas 17 Agustus 1945 Banyuwangi field from August to October 2023. This study used a Randomized Complate Block Design (RCBD) with two factors: humic acid concentration and lactobacillus bacteria, with three replications. The parameters observed were plant height, leaf number, cob weight with husk, cob weight without husk, fruit diameter, fruit length, and sweetness level. The results showed that the treatment factor of humic acid had a significant effect on plant height at 28 days after planting. For the parameter of leaf number, there was no significant difference at 14, 21, and 35 days after planting. On the other hand, for the treatment factor of lactobacillus bacteria, it was observed that plant height at 21 days after planting with a concentration of 20 ml/liter (B₁) showed a significant difference compared to the concentration of 40 ml/liter (B₃) and a highly significant difference compared to the concentration of 30 ml/liter (B₂). The interaction between humic acid and lactobacillus bacteria showed no significant effect on all parameters.